Investigation of the Acoustic Properties of Viscosity Standards - KAZYS, Rymantas; VOLEISIS, Algirdas; SLITERIS, Reimondas (Archives of Acoustics, 2016)
Longitudinal and shear ultrasonic wave velocities were measured versus temperature in the viscosity standards of Paragon S8000S, N30000S and Cannon N2700000. The measurements were performed by the through-transmission method at the frequency of 2 MHz. Ultrasonic pulses were sent via polymethyl methacrylate (PMMA) waveguides between the tips of which a small amount of the particular standard liquid was placed. The velocities of longitudinal and shear waves were determined to depend on the viscosity of the liquid and increase with the viscosity.